Kegiatan Ekstrakurikuler Rohani Islam (Rohis) dalam Pembentukan Karakter Religius Siswa di MAN 2 Kota Sukabumi - Parida; Asep Dudi; Dewi Mulyani (Bandung Conference Series: Islamic Education, 2022)
Abstract. This study will discuss "Islamic Spiritual Extracurricular Activities (Rohis) in Formation of Students' Religious Character at MAN 2 Sukabumi City". This study uses qualitative methods using qualitative descriptive. Collecting data through observation, interviews, and documentation. The results of this study indicate that: Planning for Islamic Spiritual (Rohis) extracurricular activities in the formation of students' religious character is carried out through (1) Provision of religious knowledge first (2) Through exemplary (3) Through habituation (4) Through coaching (5) Through MABIT (Night of Bina and Taqwa). The spiritual extracurricular activities in the formation of students' religious character are contained in (1) Habituation of Duha and Dzhur prayers in congregation (2) Morning recitations (3) NGABARIS (Ngaji Together with Rohis) (4) Tahfidz Quran (5) Dauroh Al-Quran (6) Study Muslimah (7) Recitation of Mawlid, Ratib, Dhikr and Sholawat (8) Filling in madding with Islamic themes (9) Muhadhoroh (10) Tadzkiroh (11) Monthly Majlis (12) Mahabbah Pilgrimage (13) Tadabur Alam (14) Archery (15) Mabit (16) Commemoration of Islamic Holidays. And the evaluation of spiritual activities at MAN 2 Sukabumi City is included in the evaluation of the work program. In the extracurricular Rohis at MAN 2 Sukabumi City, there is an evaluation in terms of assessment. The assessment includes process assessment and activity result assessment Abstrak. Penelitian ini akan membahas “Kegiatan Ekstrakurikuler Rohani Islam (Rohis) Dalam Pembentukan Karakter Religius Siswa Di MAN 2 Kota Sukabumi”. Penelitian ini menggunakan metode kualitatif dengan menggunakan deskriptif kualitatif. Pengumpulan data melalui observasi, wawancara, dan dokumentasi. Dari hasil penelitian ini menunjukkan bahwa: Perencanaan kegiatan ekstakurikuler Rohani Islam (Rohis) dalam pembentukan karakter religius siswa dilakukan melalui (1) Pembekalan ilmu agama terlebih dahulu (2) Melalui keteladanan (3) Melalui pembiasaan (4) Melalui pembinan (5) Melalui MABIT (Malam Bina dan Taqwa). Adapun Kegiatan Ekstakurikuler Rohis dalam pembentukan karakter religius siswa terdapat dalam (1) Pembiasaan Shalat Duha dan Dzhur berjamaah (2) Tilawah pagi (3) NGABARIS (Ngaji Bareng Rohis) (4) Tahfidz Quran (5) Dauroh Al-Quran (6) Kajian Muslimah (7) Pembacaan Maulid, Ratib, Dzikir dan Sholawat (8) Mengisi madding dengan tema Islami (9) Muhadhoroh (10) Tadzkiroh (11) Majlis Bulanan (12) Ziarah Mahabbah (13) Tadabur Alam (14) Panahan (15) Mabit (16) Peringatan Hari Besar Islam. Dan evaluasi kegiatan rohis di MAN 2 Kota Sukabumi termasuk kedalam evaluasi program kerja. Dalam ekstakurikuler Rohis di MAN 2 Kota Sukabumi terdapat evaluasi dari sisi penilain. Penilaian tersebut mencakup penilaian proses dan penilaian hasil kegiatan.